From Field to Food: Assessing Health Risks from Pesticide Use and Residues in the Nepalese Agri-Food System - Ghimire, Mayanath; Neupane, Dasarath; Dhital, Krishna Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: The widespread and often unsafe use of synthetic pesticides in Nepalese agriculture poses a significant threat to human health, despite its role in boosting crop yields. Objective: This review aims to assess the impacts of agricultural pesticide use on the health of rural populations in Nepal. Methods: A systematic literature review was conducted, analyzing scientific articles published between 2019 and 2025, sourced from databases like Google Scholar. Findings: The study found that Nepalese farmers frequently use highly hazardous pesticides with inadequate safety measures, leading to direct exposure and acute health symptoms (e.g., dizziness, skin irritation). Chronic exposure is linked to severe long-term health consequences, including cancer, neurological disorders, and respiratory illnesses. Pesticide residues in food further extend these risks to consumers. Conclusion: Unsafe pesticide practices in Nepal result in serious health repercussions for rural communities, underscoring an urgent need for intervention. Implication: There is a critical need for stricter pesticide regulations, comprehensive farmer education on Integrated Pest Management (IPM) and safe handling, and a promotion of sustainable agricultural alternatives.